FAKTOR DETERMINASI STRUKTUR MODAL (Studi Kasus Perusahaan Manufaktur BEI tahun 2005-2008) - Subagyo, Herry (Jurnal Ilmiah Telaah Manajemen, 2009)
This study aimed to examine factors that affect to capital structure policy on manufacturing companies in Indonesia Stock Exchange.By concept factors that determine capital structure can be dividedinto two factors, Macroeconomics and Microeconomics.Macroeconomic factors are factors that Unconrtollable which in this study proxied by Inflation, Interest Rates and Economic Growth.Microeconomicfactors are factors that can be controlled, in this study proxied by profitability, company size, Intangible Assets and Retained Earnings. Statistical test results showed that all indicators Macroeconomic factorsinfluence capital structure policy, while indicators Microeconomic factors, not all affecting capital structure.Keywords: Capital Structure, Macroeconomics, Microeconomics.